Keberadaan Ilmu Komunikasi dan Perkembangan Teori Komunikasi dalam Peradaban Dunia - Winda Kustiawan; Juni Hidayati; Vania Daffa; Alya Hamzah; Muhammad Harmain; Andika Fadli; Eki Kuswananda (Prodi Perpustakaan dan Sains Informasi, 2021)
Communication theory is a win-win solution or a guide for humans to help understand and study phenomena, symptoms, and communication processes. This study aims to explore the existence of communication science and the development of communication theory in world civilization. The approach used is a qualitative method, namely literature study, which is carried out by studying book references, articles, and browsing the internet. Collecting data by utilizing this bibliography is so that it can better support the object of research.